2021
DOI: 10.2217/nnm-2021-0040
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Silica Nanoparticles From Olive Residue and Investigation of Their Anticancer Potential

Abstract: Aim: To synthesize silica nanoparticles (SNPs) from olive residue with anticancer properties. Methods: SNPs were synthesized from olive residue ash (ORA). After characterization, cytotoxicity of the SNPs was assessed in vitro, with measurement of reactive oxygen species (ROS) levels. Results: The average diameter of the synthesized SNPs was 30–40 nm, and zeta potential analysis suggested they were stable. The synthesized SNPs were less cytotoxic than commercially available SNPs against fibroblast cells, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…The enhanced cytobiocompatibility of green synthesized OE-Ag NPs with hMSC cells and 293T cells might be resulted because of the existence of biological active and biocompatible secondary metabolites of the plant leaf extract. The similar finding on the biocompatible nature of plant leaf extract and enhanced cytobiocompatibility of the nanoparticles after the inclusion of secondary metabolites on their surface were also reported by [58,59].…”
Section: Biocompatibility Analysissupporting
confidence: 85%
“…The enhanced cytobiocompatibility of green synthesized OE-Ag NPs with hMSC cells and 293T cells might be resulted because of the existence of biological active and biocompatible secondary metabolites of the plant leaf extract. The similar finding on the biocompatible nature of plant leaf extract and enhanced cytobiocompatibility of the nanoparticles after the inclusion of secondary metabolites on their surface were also reported by [58,59].…”
Section: Biocompatibility Analysissupporting
confidence: 85%
“…Some of these works evaluated the mixing efficiency and merging of microparticles into a magnetic platform [ 29 ]. However, because these platforms provide manipulation conditions for a single droplet, they are not suitable for processes such as drug screening, which require high-throughput droplet formation [ 30 ]. Magnetic stirring inside the droplet is an alternative way to enhance the mixing.…”
Section: Introductionmentioning
confidence: 99%
“…Immobilization of bioactive and compatible biomolecules on the surface of LEVB-Ag NAPs may have contributed to their better cytobiocompatibility with normal cell lines. Another study found that immobilizing physiologically active phytoconstituents from plant extracts on the surface of silica NAPs improved their cytobiocompatibility ( Rezaeian et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%